Contact and Portuguese‐lexified creoles - Cardoso, Hugo C. (2022)
Portuguese‐lexified creoles (PLCs) include some of the oldest of the European‐lexified creoles which developed out of the colonial expansion of the Early Modern Age. This chapter describes in detail the current and past distribution of the PLCs. It surveys diachronic proposals applicable within subgroups of PLCs. The chapter focuses on theories that imply the influence of a PLC or Portuguese‐lexified pidgin on contact languages currently not classified as Portuguese‐lexified. One of the most interesting effects of the inaugural role of Portuguese in the European global linguistic expansion of the Modern Age is that, for various reasons and to different degrees, Portuguese often came to impact the linguistic repertoire of the colonizers who followed and, on many occasions, occupied places where this language had already created roots. Wherever PLCs have remained in close contact with Portuguese, a number of different trajectories can be identified.